'Than' = ' More' + Exhaustivity: Evidence from Circassian - Bylinina, Lisa; Lander, Yury (Proceedings of the Amsterdam Colloquium, 2013)
This paper discusses new facts on comparative constructions in Circassian languages that contribute to a theoretical debate about the semantics of comparatives. We argue that Circassian comparatives provide the direct evidence for the combination of two recent insights into comparative semantics: the theory of two loci of degree quanti cation in such constructions [1, 9] and theories postulating exhaustivity or maximisation at the edge of the standard clause [2].